2022
DOI: 10.1186/s12909-022-03792-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demographic and socio-economic factors in choosing hospitalist careers among US medical students

Abstract: Background The subspecialty of Hospital Medicine (HM) has grown rapidly since the mid-1990s. Diversity and inclusion are often studied in the context of healthcare equity and leadership. However, little is known about the factors potentially associated with choosing this career path among US medical students. Methods We analyzed the results of the Annual Association of American Medical Colleges Survey administered to Graduating medical students fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In our study, 37% of respondents reported that they had “no debt,” a number higher than the expected percentage based on recent data for graduating medical students. 17 However, a recent report on ophthalmology trainees reported similar levels of debt to our sample: 33% with no debt, 32% with $0–$200,000 of debt, and 35% with greater than $200,000 of debt. 18 Therefore, our sample was likely well representative of the overall ophthalmology trainee.…”
Section: Discussionsupporting
confidence: 63%
“…In our study, 37% of respondents reported that they had “no debt,” a number higher than the expected percentage based on recent data for graduating medical students. 17 However, a recent report on ophthalmology trainees reported similar levels of debt to our sample: 33% with no debt, 32% with $0–$200,000 of debt, and 35% with greater than $200,000 of debt. 18 Therefore, our sample was likely well representative of the overall ophthalmology trainee.…”
Section: Discussionsupporting
confidence: 63%